“The double dividend of training” – labor market effects of work-related continuous education in Switzerland - Denzler, Stefan [Verfasser]; Ruhose, Jens [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2022)
„This paper presents the first longitudinal estimates of the effect of work-related training on labor market outcomes in Switzerland. Using a novel dataset that links official census data on adult education to longitudinal register data on labor market outcomes, we apply a regression-adjusted matched difference-in-differences approach with entropy balancing to account for selection bias and sorting on gains. We find that training participation increases yearly earnings and reduces the risk of unemployment two years after the treatment. However, the effects are heterogeneous as to gender, age, education, and regional labor market context. The gains are highest for middle-aged men with formal vocational education working in either depressed or booming labor markets.“ (authors’ abstract; BIBB-Doku)

Die Studie untersucht, welchen ökonomischen Nutzen Weiterbildung in der Schweiz hat. Die Autoren zeigen, dass die Teilnahme an Weiterbildungen das Einkommen im Durchschnitt um 4,8% erhöht und das Risiko, arbeitslos zu werden, um rund 30% verringert. Die Effekte variieren recht stark nach Kontexten und Gruppen: So profitieren Arbeitnehmende mit beruflicher Ausbildung stärker von berufsbezogener Weiterbildung als Personen mit allgemeiner Ausbildung. Ebenso seien die Weiterbildungserträge höher in Regionen, die durch niedrige Beschäftigungs- und hohe Arbeitslosenquoten gekennzeichnet sind. (BIBB-Doku)
Keywords: S 1.5 Weiterbildung; 370; Weiterbildung; Weiterbildungsbeteiligung; Weiterbildungsnutzen; Bildungsinvestition; Bildungsertrag; Schweiz